Stromal Cells Structure, Function, and Therapeutic Implications - Valarmathi, Mani T. (IntechOpen, 2019)
Stromal cells are connective tissue cells of any organ, and they support the function of the parenchymal cells of that particular organ. Stromal/stromal stem cells are fundamentally a heterogeneous population of cells with contradictory differentiation potential depending upon their environmental niche. Stromal cell biology is not only intriguing, but equally stromal cell ontogeny in vivo remains challenging. In recent years there has been substantial advances in our understanding of stromal cell biology, especially stromal cell isolation, characterization, differentiation, and interactions in physiological (epithelial-stromal interactions) as well as pathophysiological (stromal-cancer interactions) contexts. In addition, stromal cells are also utilized more and more as a therapeutic tool not only in the field of gene therapy but also in the translational field of tissue engineering and regenerative medicine. Therefore, the goal of this book is to consolidate the recent advances in the area of stromal/stromal stem cell biology covering a broad range of interrelated topics in a timely fashion and to disseminate that knowledge in a lucid way to a greater scientific audience. This book will prove highly useful for students, researchers, and clinicians in stem cell biology, developmental biology, cancer biology, pathology, oncology, as well as tissue engineering and regenerative medicine. This quick reference will benefit anyone desiring a thorough overview of stromal cell structure, function, and its therapeutic implications.